Trends of ocular fungal infections in North China (2001-2020) - Jiamin Liu; Zhenyu Wei; Kai Cao; Zijun Zhang; Xizhan Xu; Qingfeng Liang (Elsevier, 2023)
Objectives: To analyze the epidemiologic features, culture positivity, the fungal spectrum of different sites of ocular infection in North China over 20 years from 2001 to 2020. Methods: 11, 635 patients suspected of ocular fungal infection were reviewed. The demographic profile, fungal positive culture rate among different sites, the distribution, and trends of main pathogens among cornea and intraocular fluid were analyzed. Results: Among 11, 635 samples, the positive culture rate of ocular fungal infection was 23.6%. Most of samples (83.1%) were from cornea, and their culture positivity was 26.9%. Fungal keratitis occurred more often during the harvesting season (October to December; 34.0%) than in other seasons (average: 22.0%). Fusarium sp. (53.2%), Aspergillus sp. (15.9%) and Alternaria sp. (12.5%) were the most common fungal species of ocular mycotic infections in the past two decades in north China. 2562 organisms were identified from cornea, of which 1443 (56.3%) were Fusarium sp., 403 (15.7%) and 329 (12.8%) were Aspergillus sp., and Alternaria sp., respectively. Of the 120 fungi isolated from the intraocular fluid, the most common was Aspergillus sp. (33.3%), followed by Fusarium sp. (24.2%) and Candida sp. (15.0%). Conclusions: Fusarium sp., Aspergillus sp. and Alternaria sp. were the most common organisms in cases of fungal keratitis, while Aspergillus sp., Fusarium sp. and Candida sp. were the most frequent isolates for fungal endophthalmitis.